Telephone consultations with otolaryngology – head and neck surgery reduced emergency visits and specialty consultations in northern Alberta - Peter George Jaminal Tian; Dean Eurich; Hadi Seikaly; Douglas Boisvert; John Montpetit; Jeffrey Harris (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background RAAPID (Referral, Access, Advice, Placement, Information, and Destination) is a 24-h call center in Alberta, Canada, facilitating urgent telephone consultations between physicians and specialists. We evaluated the extent to which RAAPID calls to Otolaryngology-Head and Neck Surgery (OHNS) reduced visits to the emergency department and specialty clinics. Methods This was a cross-sectional study evaluating all telephone consultations to OHNS from physicians in northern Alberta between 2013 and 2014 (T1) (where consultations by residents occurred) and 2015 to 2017 (T2) (where consultations were done by consultants during office hours and residents during after hours). Outcomes of the calls included medical advice, specialty clinic referrals, and emergency department (ED) referrals. Differences in the reduction of ED visits and costs, overall as well as in T1 and T2, were assessed using multivariate logistic regression. Results Overall, 62.3% (1064/1709) of telephone consultations reduced ED visits consisting of advice being provided (n = 884; 83.1%) and referral to specialty clinics (n = 180; 16.9%). The adjusted odds ratio of calls reducing emergency visits in T2 as compared to T1 was 2.47 (95% CI 1.99 to 3.08). The adjusted odds ratio of reducing ED visits during office hours compared to after-hours 2.54 (95% CI 1.77–3.64). The estimated direct costs avoided from ED visits in T1 and T2 were $42,224.22 and $114,393.86, respectively. Conclusion RAAPID telephone consultations to OHNS were effective in reducing ED visits and healthcare costs. This model should be considered in other areas to improve efficiencies within the health system.